Global Marketing of Agricultural and Mineral Products, Pre-Requisite for Africa’s Economic Development - Ibidunni, O.S. (Richtmann Publishing, 2013)
The study was on global marketing of agricultural and mineral products for economic development of African countries. Exportactivities of the fifty-three member countries of the Continent, with particular focus on the five North African countries makingup Arab Maghreb Union (AMU) were investigated. Relevant literatures, with theories, were explored to substantiate the study.Qualitative method of research was adopted using secondary data. Africa: intra-regional export trade statistics by countrieswere sourced; for 2006 to 2008. Measures of central tendency, dispersion, skewness and kurtosis; and the relationship inbetweenthem were highlighted to bring out the required results needed from the study. Data were expressed in United State ofAmerica, (US) billion dollars. Findings revealed that Africa was so endowed with abundant natural resources, expanse ofuncultivated fertile land, skilled and unskilled labour, water and unexplored mineral deposits. Products from agriculture andminerals are mostly for subsistence while the exportable ones are not being produced mechanically. It was recommended thatAfrica should move beyond international marketing as global marketing guarantees abundant production of quality products forexports, the regional economic communities should be united in their regional policies and programmes to foster specializationand optimal productivity of the representative country’s products.